The books of Nahum, Habakkuk, and Zephaniah - Robertson, O. Palmer (Grand Rapids, Mich. : W.B. Eerdmans, 2018)
The close-knit bond between prophecy and history, according to O. Palmer Robertson, becomes particularly clear through the study of Nahum, Habakkuk, and Zephaniah. As the historical context of their messages is explored, it becomes ever more apparent that biblical history in addition to providing the context for prophecy actually embodies and functions as prophecy. The events that occurred to Judah and its neighbors spoke in anticipation of world-shaking circumstances that were yet to come.
In this commentary Robertson combines the insights of biblical theology with a keen awareness of the age in which we live. After first dealing with the relevant background issues of Nahum, Habakkuk, and Zephaniah redemptive-historical setting, theological perspective, date and authorship, and so on Robertson applies the care and precision of an exegete and the concern of a pastor to his verse-by-verse exposition of each book. The result is a relevant confrontation with the ancient call to repentance and faith a confrontation greatly needed in todays world.
The book of Nahum -- Superscription (1:1) -- Public announcement of Nineveh's judgment (1:2-14) -- Dramatic depiction of Nineveh's judgment (2:1-14 [Eng. 1:15--2:13]) -- The surety of Nineveh's judgment (3:1-19) -- The book of Habakkuk -- Superscription (1:1) -- The dialogue of protest (1:2-17) -- The resolution of wisdom (2:1-20) -- A psalm of submission (3:1-19) -- The book of Zephaniah -- Superscription (1:1) -- Cosmic covenantal judgment comes with Yahweh's great day (1:2-18) -- The call to repentance sounds before the arrival of God's great day (2:1-15) -- God reconstitutes his people with the arrival of that great day (3:1-20).
Includes bibliographical references (pages 46-52) and indexes.
Keywords: Bible.OT -- Commentaries; Bible.OT -- Commentaries; Bible.OT -- Commentaries